2020
DOI: 10.2196/18076
|View full text |Cite
|
Sign up to set email alerts
|

Wikipedia in Vascular Surgery Medical Education: Comparative Study

Abstract: Background Medical students commonly refer to Wikipedia as their preferred online resource for medical information. The quality and readability of articles about common vascular disorders on Wikipedia has not been evaluated or compared against a standard textbook of surgery. Objective The aims of this study were to (1) compare the quality of Wikipedia articles to that of equivalent chapters in a standard undergraduate medical textbook of surgery, (2) id… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 15 publications
0
16
0
Order By: Relevance
“…By June 2021, the number of online medical users in China was 239.33 million, and the utilization rate of the internet was 23.7%, an increase of 11.4% over December 2020 [ 29 ]. In an analysis of internet search trends in China, some scholars found that only 43.74% of the search results for PE were related to PE [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…By June 2021, the number of online medical users in China was 239.33 million, and the utilization rate of the internet was 23.7%, an increase of 11.4% over December 2020 [ 29 ]. In an analysis of internet search trends in China, some scholars found that only 43.74% of the search results for PE were related to PE [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Wikipedia is a popular resource among medical students [ 9 , 10 , 25 ], but its reliability is debated [ 26 ]. Arguments against Wikipedia as a resource cite poor quality of images [ 16 ] and insufficient detail [ 15 , 16 , 27 ]. London et al [ 14 ] found that Wikipedia was generally accurate and complete for basic anatomical information, despite asserting that textbooks should still be considered the gold standard.…”
Section: Discussionmentioning
confidence: 99%
“…The DISCERN instrument, which is a tool for judging the quality of health information on treatment choices, was used to assess the quality of the articles retrieved from Wikipedia and Baidu Encyclopedia ( 21 ); however, its actual function is a matter of debate. Some scholars have argued that the original version of the DISCERN instrument is not suitable for evaluating Wikipedia articles ( 22 , 23 ); however, a great deal of recent research has still used the DISCERN instrument to evaluate the quality of online Wikipedia articles ( 15 , 16 ). Thus, in the absence of a better tool, the DISCERN instrument was considered an appropriate tool for evaluating the quality of the Wikipedia online articles.…”
Section: Methodsmentioning
confidence: 99%
“…The higher DISCERN score, the better the quality of the article. Overall, a total DISCERN score can range from 16 to 80, and based on the total score, the articles are categorized as very poor (a score of [16][17][18][19][20][21][22][23][24][25][26], poor (a score of 27-38), fair (a score of 39-50), good (a score of 51-62), and excellent (a score of 63-80) (15,16).…”
Section: Assessment Of the Quality Of The Research Articlesmentioning
confidence: 99%
See 1 more Smart Citation